Sosialisasi Peran Guru dalam Pengembangan Literasi dan Numerasi pada Anak Usia Dini di BKB Kemas Mekar Jaya - Hidayat, Amat; Junedi, Beni; Astuti, Astuti; Khoirunnisa, Khoirunnisa; Munawaroh, Roudatul; Masruroh, Masruroh; Sutihat, Kaifa; Mabrukah, Ratu; Refiati, Refiati; Irmayanti, Irmayanti (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Early childhood literacy and numeracy development is an important foundation in building sustainable learning skills. Teachers have a crucial role in guiding and facilitating children in starting their literacy and numeracy journey. This article presents the results of community service activities in the form of socialization regarding the role of teachers in developing literacy and numeracy at BKB (Bina Keluarga Balita) Kemas Mekar Jaya. The methods used in this service include lectures, discussions, and learning simulations. The results of the service show that after the socialization, teachers and caregivers at BKB better understand the importance of an age-appropriate approach, and are able to apply creative techniques to increase children's interest in literacy and numeracy. Challenges faced include limited facilities and a lack of initial understanding of the importance of numeracy development. In conclusion, this socialization succeeded in increasing teachers' knowledge of their role in developing literacy and numeracy in early childhood and paved the way for further collaboration.